Exploration of the Teaching of Mental Health Education Courses in Fine Art Colleges and Universities From the Perspective of Positive Psychology - Zhang, Yi (Frontiers in Psychology, 2022)
The study’s objective is to examine the impact of teacher ability on student academic performance, identification (self-valued goals; personal importance), and self-regulation skills. Additionally, the study examines the mediating effect of identification (self-valued goals; personal importance) and self-regulation skills between teacher ability and student academic performance. The data was collected by the teachers at different colleges and universities in China and 341 samples were used to analyze the data through a convenient sampling technique. Moreover, partial least square structural equation modeling is used in data analysis with Smart PLS software. This research indicates that teacher ability has a positive and significant effect on student academic performance, identification (self-valued goals; personal importance), and self-regulation skills. Further, the study also discovers that identification (self-valued goals; personal importance) and self-regulation skills significantly mediate between teacher ability and student academic performance. The study is helpful for the teachers to adopt the better strategies and abilities in themselves when they are engaged with the student in teaching activities.